2021
DOI: 10.3390/ijms22189968
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Tamarind Trypsin Inhibitor in Chitosan–Whey Protein Nanoparticles on Hepatic Injury Induced High Glycemic Index Diet: A Preclinical Study

Abstract: Several studies have sought new therapies for obesity and liver diseases. This study investigated the effect of the trypsin inhibitor isolated from tamarind seeds (TTI), nanoencapsulated in chitosan and whey protein isolate (ECW), on the liver health status of the Wistar rats fed with a high glycemic index (HGLI) diet. The nanoformulations without TTI (CW) and ECW were obtained by nanoprecipitation technique, physically and chemically characterized, and then administered to the animals. The adult male Wistar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 87 publications
(184 reference statements)
0
11
0
Order By: Relevance
“…Another study with the TTI, nanoencapsulated in chitosan, and isolated whey proteins, showed that Wistar rats fed the HGLI diet exhibited a significantly lower fasting plasma glucose concentration, without changing the insulin concentration compared to the group of untreated Wistar rats, which also consumed the same HGLI diet [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study with the TTI, nanoencapsulated in chitosan, and isolated whey proteins, showed that Wistar rats fed the HGLI diet exhibited a significantly lower fasting plasma glucose concentration, without changing the insulin concentration compared to the group of untreated Wistar rats, which also consumed the same HGLI diet [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the protection of TTI observed in ECW in the present study and others, in addition to the low toxicity [ 13 , 14 , 15 ] and the bioactive potential of ECW evidenced in animals with obesity [ 15 , 16 ], in the present study, we investigated and compared the effects of TTI and ECW on dietary intake, weight, Lee index, biochemical, and inflammatory parameters in Wistar rats with diet-induced obesity.…”
Section: Discussionmentioning
confidence: 87%
“…Queiroz et al [ 13 ] synthesized and characterized ECW, and, posteriorly, other preclinical studies were conducted with this nanoformulation using the same method of obtaining [ 14 , 15 , 16 ]. In the present study, TTI and ECW presented the same physicochemical characteristics and encapsulation efficiency, similar to previous studies [ 5 , 6 , 7 , 9 , 13 , 14 , 15 , 16 ]. Thus, it demonstrated the method’s reproducibility and guaranteed it was the same nanoparticle in question.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations